Making sense of corporate social responsibility : exploring organizational processes and strategies - Heijden, A.J.W. van der; Driessen, P.P.J.; Cramer, J.M. (Elsevier, 2010)
This article describes and analyzes how company members make sense of Corporate Social Responsibility (CSR). The research question focuses on organizational processes of structuring CSR in practice: How do CSR sensemaking processes in companies work and is it possible to discern process strategies? Based on universal sensemaking theories, a conceptual framework is developed to analyze CSR sensemaking in practice. When the framework is used to analyze the experiences of 18 companies we are able to characterize internal CSR sensemaking as a process that consists of a three-stage cycle with an important role for change agents. Further, we conclude that the companies develop unique interpretations of the three-stage cycle. Grouping the processes, we discern two strategies of communicating and acting that stimulate the involvement of people and embed CSR values in the company.
Keywords: Milieukunde; CSR; Corporate Social Responsibility; Change agents; Organizational sensemaking processes